Lewis Pair Polymerization of Epoxides via Zwitterionic Species as a Route to High‐Molar‐Mass Polyethers. Issue 31 (27th June 2019) - Walther, Patrick; Krauß, Annabelle; Naumann, Stefan
Abstract: A dual catalytic setup based on N‐heterocyclic olefins (NHOs) and magnesium bis(hexamethyldisilazide) (Mg(HMDS)2 ) was used to prepare poly(propylene oxide) with a molar mass ( M n ) >500 000 g mol −1, in some cases even >10 6 g mol −1, as determined by GPC/light scattering. This is achieved by combining the rapid polymerization characteristics of a zwitterionic, Lewis pair type mechanism with the efficient epoxide activation by the Mg II species. Transfer‐to‐monomer, traditionally frustrating attempts at synthesizing polyethers with a high degree of polymerization, is practically removed as a limiting factor by this approach. NMR and MALDI‐ToF MS experiments reveal key aspects of the proposed mechanism, whereby the polymerization is initiated via nucleophilic attack by the NHO on the activated monomer, generating a zwitterionic species. This strategy can also be extended to other epoxides, including functionalized monomers. Abstract : So long ! Poly(propylene oxide) with exceptionally high molar mass can be prepared with a catalytic setup consisting of a nucleophilic N ‐heterocyclic olefin and a magnesium‐based Lewis acid. The magnesium species activates the monomer for attack by the olefin, resulting in a rapid, Lewis pair type polymerization via zwitterionic species.